Agave fructans as fat and sugar replacers in ice cream: Sensory, thermal and texture properties. (November 2020) - Jardines, A. Pintor; Arjona-Román, J.L.; Severiano-Pérez, P.; Totosaus-Sánchez, A.; Fiszman, S.; Escalona-Buendía, H.B.
Abstract: The principal aim of the present study was to investigate the feasibility of replacing fat and sugar with agave fructans to produce both low-fat, and low-fat and sugar ice cream. For this purpose, agave fructans (0–3.0%) were added to several ice cream formulations to explore relationships between their sensory perception, and their previously reported thermal and texture properties. Formulations with less than 1.2% of agave fructans contributed sensory attributes linked to the amount and size of ice crystals, such as crystallized (both texture and appearance), grainy and cold sensation. These were related to frozen water, ice fraction, enthalpy and maximum temperature, as well as hardness, melting rate and compression force. On the other hand, the samples with concentrations between 1.2 and 3.0% of agave fructans showed ice cream formulations with longer melting times, smooth, creamy and fluid texture, and with fatty sensation. These properties were directly related to low non-frozen water concentrations, high glass transition temperatures and ΔCp values, as well as textural properties, such as apparent viscosity and overrun. Even though consumers liked the samples with higher amounts of fat and sugar, all the samples showed liking values in a quite narrow range around the neutral point on the liking scale. Thus, agave fructans were able to enhance several sensory, thermal and textural properties, making them a feasible alternative as a fat and sugar replacer. Graphical abstract: Image 1 Highlights: Agave fructans modified significantly the sensory properties in ice cream. 3.0% of fructans contributed longer melting times, and smooth, creamy and fatty sensations. Sensory attributes correlated with thermal and texture properties. Thermal and texture properties are influenced by water mobility as affected by agave fructans.